Tribocorrosion: Ceramic and Oxidized Zirconium vs Cobalt-Chromium Heads in Total Hip Arthroplasty - Tan, Sok Chuen; Lau, Adrian C.K.; Del Balso, Christopher; Howard, James L.; Lanting, Brent A.; Teeter, Matthew G. (The Journal of arthroplasty, 2016)
This matched-cohort study aims to compare tribocorrosion between matched ceramic and cobalt-chromium femoral head trunnions and between matched Oxinium and cobalt-chromium femoral head trunnions. Secondary objectives were to investigate whether taper design, depth of trunnion, implantation time, age, body mass index, and gender have an effect on fretting and corrosion. All hip prostheses retrieved between 1999 and 2015 at one center were reviewed, giving a total of 52 ceramic heads. These were matched to a cobalt-chromium cohort according to taper design, head size, neck length, and implantation time. The trunnions were examined by 2 observers using a 4-point scoring technique and scored in 3 zones: apex, middle, and base. The observers were blinded to clinical and manufacturing data where possible. A separate matched-cohort analysis was performed between 8 Oxinium heads and 8 cobalt-chromium heads, which were similarly scored. Ceramic head trunnions demonstrated a lower median fretting and corrosion score at the base zone (P < .001), middle zone (P < .001), and in the combined score (P < .001). Taper design had a significant effect on fretting and corrosion in the apex zone (P = .04) of the ceramic group, as well as the cobalt-chromium group (P = .03). Between Oxinium heads and cobalt-chromium heads, there was no significant difference in the fretting and corrosion score across all 3 zones (base: P = .22; middle: P = .92; and apex: P = .71) and for the combined score (P = .67). This study shows that ceramic head confers an advantage in trunnion fretting and corrosion. Taper design and implantation time were also significant factors for fretting and corrosion.